Comparative Effects of Adapted Taekwondo Versus Tai Chi on Health Status in Independent Older Women: A Randomized Controlled Trial - Sanchez-Ramirez, C; Herrera-Valenzuela, T; Cid-Calfucura, I; Pavez-Lizarraga, A; Flandes-Vargas, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Taekwondo (TKD) and Tai Chi (TC) are promising interventions for enhancing health and physical function in older people, yet few studies have compared their effects across multiple domains. This study aimed to compare the effects of TKD versus TC on health status in independent older women. Methods: A randomized controlled trial was conducted with two parallel groups: TKD (n = 11) and TC (n = 10). Both groups trained three times per week for 8 weeks. Pre- and post-intervention assessments included anthropometry, submaximal CPX, 2-min step test, Timed Up-and-Go (TUG), isometric mid-thigh pull (IMTP), maximal isometric handgrip strength (MIHS), 30 s chair stand, 30 s arm curl, sit-and-reach, and back scratch. Results: Compared with TC, the TKD group showed significantly greater improvements in several cardiorespiratory outcomes, including VO2 at VT1 and VT2, power output, VO2/HR, OUES, and VE/VCO2 slope (p < 0.05 to p < 0.001; d = 0.69–1.29). TKD participants also exhibited superior gains in maximal and relative IMTP, MIHS, relative MIHS, 30 s arm curl repetitions, and TUG performance (p < 0.05 to p < 0.001; d = 0.61–1.26). Both groups improved similarly in the 30 s chair stand test (p < 0.05). Flexibility outcomes diverged, with TKD improving sit-and-reach and TC showing greater gains in the back scratch test (p < 0.05). Conclusions: TKD was more effective than TC in improving cardiorespiratory fitness, muscle strength, and balance in older women and may represent a valuable health-oriented training strategy for this population. © 2025 by the authors.
Keywords: physical activity; combat sports; older adults; healthy aging